WOMEN AND HOMELAND IN THEATRICAL PLAYS DURING EARLY REPUBLICAN PERIOD - Gülay YURT (Fırat University, 2019)
In the Turkish literature, in the subject areas regarding the National Struggle there is a huge dedication to the women heroism. In heroic stories, during the period integration of the country and the nation, the subject of theatrical pays tried to emphasize the important role of women. This study will discuss the approaches of theatrical plays regarding woman's homeland defence in early Republican period, penned between the years 1923-1950. Women should be at the front if necessary even in the rear displaying the struggle and the success through examining the role she assumed in theatrical plays.